Inflammatory breast cancer: Study of 53 cases. Diagnostic and treatment guidelines - Viola Alles, Alberto; Vasallo, Alberto (Cirugía del Uruguay, 1982)
The authors make a brief histórica! review and define the disease. 1,359 breast cancers were examined. 53 were inflamatory cancers which accounts for a frequency of 3.9%. A detailed analysis of the different parameters is made. The authors insist on a correct nosological evaluation of the regional and distant lesions. They emphasize the need for a skin biopsy. The usefulness of thermography as a prognostic parameter as well as eventual surgery are emphasized. The determination of honnone receptors and immunological typification are discussed. A guide line for a rational treatment of the disease is presented.